Identification of Genomic Regions Associated with Peanut Rust Resistance by Genome-Wide Association Studies - Xinlong Shi; Ziqi Sun; Feiyan Qi; Suoyi Han; Yixiong Zheng; Wenzhao Dong; Maoning Zhang; Xinyou Zhang (Plants)
Peanut rust, caused by Puccinia arachidis Speg., is one of the most significant leaf diseases globally, and has a severe impact on peanut yield and quality. The development of disease-resistant varieties is recognized as an effective strategy to mitigate the damage caused by peanut rust. However, the research foundation for understanding peanut rust remains relatively limited. In this study, we identified significant single nucleotide polymorphisms (SNPs) associated with peanut rust resistance using a natural population consisting of 353 peanut germplasm accessions. These accessions were analyzed based on resequencing data and rust disease phenotypes across one laboratory test and three field trials. A total of 18 significant SNPs were identified on chromosomes A05 (5 SNPs), A08 (7 SNPs), and A12 (6 SNPs). Notably, three SNPs—Arahy.05_93085395, Arahy.05_93114354, and Arahy.12_4097252—were consistently detected across multiple environments. Within their confidence intervals, 48 genes were annotated, including 9 NLR domain-containing genes functionally related to plant disease resistance, which may serve as candidate genes for peanut rust resistance. This study provides insights into the regulatory mechanisms underlying peanut rust resistance.